Spinoffs versus buyouts: Profitability of alternate routes for commercializing innovations. (20th December 2013) - Rubera, Gaia; Tellis, Gerard J.
<x xml:space="preserve">Abstract</x> This research compares the performance of spinoffs and buyouts divested to commercialize innovations. The authors study 145 spinoffs and 121 buyouts that occurred in the United States between 1996 and 2005. Analysis provides three critical findings. First, spinoffs have higher profits in the two years after divestiture; afterwards, buyouts have higher profits. Second, strategic emphasis (investment in R&D versus marketing) is the mechanism that explains the diverging profitability of spinoffs and buyouts over time. Third, this occurs through two routes: a one‐step mediated effect via strategic emphasis; a two‐step mediated effect via strategic emphasis and radicalness. Copyright © 2013 John Wiley & Sons, Ltd.